Static modeling of the reservoir for estimate oil in place using the geostatistical method - Amanipoor, Hakimeh (Geodesy and Cartography, 2019)
Three-dimensional simulation using geostatistical methods in terms of the possibility of creating multiple realizations of the reservoir, in which heterogeneities and range of variables changes are well represented, is one of the most efficient methods to describe the reservoir and to prepare a 3D model of it and the results have been used as acceptable results in the calculations due to the high accuracy and the lack of smoothing effect in small changes compared to the results of Kriging estimation. The initial volumetric tests of the Hendijan reservoir in southern Iran were carried out according to the construction model and the petrophysical model prepared by the software and according to the fluid contact levels, and the ratio of net thickness to total thickness in different reservoir zones. The calculations can be distinguished based on the zoning of the reservoir and also on the basis of type of facies. Accordingly, the average volume of fluid in place of the field is calculated in different horizons. The results of the simulation showed that the Ghar reservoir rock has gas and Sarvak Reservoir has the largest amount of oil in place.